INTEGRATING LANGUAGE AND CULTURE IN LANGUAGE SKILL CLASSES - Bahri, Seful (Language Circle: Journal of Language and Literature, 2015)
Foreign language learning is foreign culture learning. It also means that the teaching of culture should become an integral part of the teaching of a language. Culture teaching should allow learners to increase their knowledge of the target culture in terms of people‘s way of life, values, attitude, and beliefs, and how these manifest in lnguistics categories and forms. These things are the concerns of this article and will be elaborated in the explanations of the relationship between language and culture, the ways they are taught integratedly, and simple procedure in carrying out classroom activities.